An Algorithm for Cavity Reconstruction in Electrical Impedance Tomography (Communications in Mathematical Research, 2021)
We consider the inverse problem of finding cavities within some objectfrom electrostatic measurements on the boundary. By a cavity we understand anyobject with a different electrical conductivity from the background material of thebody. We give an algorithm for solving this inverse problem based on the outputnonlinear least-square formulation and the regularized Newton-type iteration. Inparticular, we present a number of numerical results to highlight the potential andthe limitations of this method.
Keywords: electrical impedance tomography; conductivity; Levenberg-Marquardt (L-M) algorithm.